Stigma Reduction Among African American Women With HIV: UNITY Health Study. (1st July 2018) - Rao, Deepa; Kemp, Christopher G.; Huh, David; Nevin, Paul E.; Turan, Janet; Cohn, Susan E.; Simoni, Jane M.; Andrasik, Michele; Molina, Yamile; Mugavero, Michael J.; French, Audrey L.
Abstract : Introduction: African American women encounter disproportionately high rates of HIV-related morbidity and mortality, which is partially mediated through stigma and its effect on HIV treatment adherence. Objective: To assess the effect of the UNITY peer support workshop on HIV-related stigma among African American women living with HIV, compared with a time and attention control group. Methods: African American women living with HIV were randomized to the UNITY workshop or a breast cancer education control group. Interventions took place in HIV clinics in Chicago, IL and Birmingham, AL. Participants self-reported HIV-related stigma and social support at baseline, after workshop, and at 4 follow-up visits over 12 months. Results: Two hundred thirty-nine participants (UNITY n = 124; breast cancer education n = 115) were assessed over 1 year. Both arms experienced decreases in mean stigma scores over time. Our model estimated that allocation to UNITY was not associated with a significant difference in stigma points over time. Post hoc analysis suggested that preceding increases in perceived social support are associated with decreased HIV-related stigma in this population. Conclusions: Although UNITY did not significantly reduce HIV-related stigma in this population, our findings suggest that social support may be key to HIV-related stigma reduction. Abstract : Supplemental Digital Content is Available in the Text.